1996
DOI: 10.1002/(sici)1097-0142(19960115)77:2<321::aid-cncr15>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise abnormality of sex steroid hormone receptors, tumor suppressor gene products (p53 and Rb), and cyclin E in uterine endometrioid carcinoma

Abstract: In the development of endometrial carcinoma, stepwise abnormalities of sex steroid receptors, tumor suppressor gene products, and cyclins apparently exist, and may correlate with the progression of the malignant process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…The present study also demonstrates that there are no apparent differences in p53 gene in UL. A similar observation was reported in another sex steroid-dependent tumor, uterine endometrioid carcinoma, in which there were no changes in p53 level between endometrioid carcinoma and the adjacent tissue (Li et al, 1996). Ours and other some studies have confirmed that there has been no significant association between p53 loss and UL.…”
Section: Discussionsupporting
confidence: 90%
“…The present study also demonstrates that there are no apparent differences in p53 gene in UL. A similar observation was reported in another sex steroid-dependent tumor, uterine endometrioid carcinoma, in which there were no changes in p53 level between endometrioid carcinoma and the adjacent tissue (Li et al, 1996). Ours and other some studies have confirmed that there has been no significant association between p53 loss and UL.…”
Section: Discussionsupporting
confidence: 90%
“…4) Thus, overexpression of cyclin E/CDK2 is theoretically oncogenic. In our study, only a limited number of cyclin E-positive cells was observed in the normal squamous epithelia, whereas considerable numbers of cells in severe epithelial dysplasia and SCCs overexpressed cyclin E. While overexpression of cyclin E has also been noticed in breast, 39) endometrial, 40) uterine, 22) and lung 20,41) cancers, the role of this protein is not clear.…”
Section: Discussioncontrasting
confidence: 71%
“…Cyclin E immunostaining is a feature of most endometrial carcinomas (90). As has been demonstrated in breast cancers, an inverse correlation between positive estrogen receptor status and cyclin E immunostaining appears to exist in endometrial carcinomas, but not in adjacent normal or hyperplastic epithelium from the same patients (91). Although cyclin E is not restricted to neoplastic endometrial disorders, since increased levels of cyclin E are noted during the normal proliferative phase (92), there does appear to be an accumulation of this protein from normal through simple and complex hyperplasia to malignancy (91,93).…”
Section: Genito-urinary Tract Cancersmentioning
confidence: 72%
“…Although cyclin E is not restricted to neoplastic endometrial disorders, since increased levels of cyclin E are noted during the normal proliferative phase (92), there does appear to be an accumulation of this protein from normal through simple and complex hyperplasia to malignancy (91,93). Although correlations with serous type, grade, and stage have been suggested (91,93), the prognostic implications of cyclin E need to be studied in greater detail (90).…”
Section: Genito-urinary Tract Cancersmentioning
confidence: 99%